First Canadian experience with robotic single-incision pyeloplasty: Comparison with multi-incision technique - Law, Jeffrey; Rowe, Neal; Archambault, Jason; Nastis, Sofia; Sener, Alp; Luke, Patrick P. (Canadian Urological Association Journal, 2016)
Introduction: We compared the outcomes of single-incision, robotassisted laparoscopic pyeloplasty vs. multiple-incision pyeloplasty using the da Vinci robotic system. Methods: We reviewed all consecutive robotic pyeloplasties by a single surgeon from January 2011 to August 2015. A total of 30 procedures were performed (16 single:14 multi-port). Two different single-port devices were compared: the GelPort (Applied Medical, Rancho Santa Margarita, CA) and the Intuitive single-site access port (Intuitive Surgical, Sunnyvale, CA). Results: Patient demographics were similar between the two groups. Mean operating time was similar among the single and multi-port groups (225.2 min vs. 198.9 minutes [p=0.33]). There was no significant difference in length of hospital stay in either group (86.2 hr vs. 93.2 hr [p=0.76]). There was no difference in success rates or postoperative complications among groups. Conclusions: Single-port robotic pyeloplasty is non-inferior to multiple-incision robotic surgery in terms of operative times, hospitalization time, success rates, and complications. Verifying these results with larger cohorts is required prior to the wide adoption of this technique. Ongoing objective measurements of cosmesis and patient satisfaction are being evaluated.